Алгоритм оцінки і контролю параметрів якості обслуговування в мультисервісній мережі IP/MPLS - Климаш, М.М.; Лаврів, О.А.; Добуш, Ю.Д. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
At present, monitoring of service quality parameters presents an important task
for information networks engineering and operation. The key technology for new
generation networks is based on package transportation technology IP/MPLS and
program commutators Softswitch. Proposed is a checking algorithm for network
quality service parameters based on the efficiency of data link layer protocol.